2008
DOI: 10.1063/1.3040719
|View full text |Cite
|
Sign up to set email alerts
|

Correlating exchange bias with magnetic anisotropy in ion-beam bombarded NiFe/Mn-oxide bilayers

Abstract: The exchange bias field dependence on the Mn-oxide and its microstructure in NiFe/Mn-oxide bilayers was investigated. Transmission electron microscopy results have shown that the bilayer bottom consisted of either alpha-Mn, rocksalt MnO, or a composite of tetragonal Mn(3)O(4)+MnO, depending on the ratio of O(2)/Ar used during dual ion-beam deposition. Magnetometry results at 5 K indicate that the exchange bias field (H(ex)similar to-300 Oe) is largest in a NiFe/Mn (0%O(2)/Ar) bilayer. The MnO formation by in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The simple intuitive model [29] as well as sophisticated theories [30,31] seem to agree that the exchange bias effect should be larger for larger anisotropy of the AFM substance in a FM/AFM heterostructure which has been elaborately described by Nogués et al [3]. Although the experimental investigations [32][33][34] dealing with the role of the anisotropy seem to agree with the theories, any quantitative conclusions from them could not be established because of the difficulties for extracting the anisotropy of the AFM component from the heterostructure. In the present observation the larger EB field is found to be associated with the larger coercivity obtained from the MR-H curve which is in accordance with the proposed theories [29][30][31] as well as the experimental results [32][33][34].…”
mentioning
confidence: 72%
“…The simple intuitive model [29] as well as sophisticated theories [30,31] seem to agree that the exchange bias effect should be larger for larger anisotropy of the AFM substance in a FM/AFM heterostructure which has been elaborately described by Nogués et al [3]. Although the experimental investigations [32][33][34] dealing with the role of the anisotropy seem to agree with the theories, any quantitative conclusions from them could not be established because of the difficulties for extracting the anisotropy of the AFM component from the heterostructure. In the present observation the larger EB field is found to be associated with the larger coercivity obtained from the MR-H curve which is in accordance with the proposed theories [29][30][31] as well as the experimental results [32][33][34].…”
mentioning
confidence: 72%
“…1͑e͔͒ with a roughness of less than 2 nm was observed, similar to that of the unbombarded Mn layer. 6 This suggests strongly that possible roughness effects 1 influencing the exchange bias behavior can be excluded since all samples exhibit the same degree of surface interfacial roughness. Therefore, only variations in spin orientations modified by the Ar ion-beam bombardment can be responsible for the variations in exchange bias behavior in the film systems.…”
Section: Resultsmentioning
confidence: 98%
“…The NiFe/Mn bilayer with the dimension of 120ϫ 120ϫ 12 nm 3 ͑40ϫ 40ϫ 6 cell 3 ͒ was used. The spin structures near the interface between NiFe and Mn can be obtained by applying the anisotropy energies ͑K͒ and exchange stiffness constants ͑Aij͒ of NiFe and Mn, 6 respectively. The preliminary results have shown that in the unbombarded Mn layer ͑V EH =0 V͒, compensated AF Mn spins aligned parallel to the interface was observed ͑left panel, the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the experimental investigations [32][33][34] dealing with the role of the anisotropy seem to agree with the theories, any quantitative conclusions from them could not be established because of the difficulties for extracting the anisotropy of the AFM component from the heterostructure. In the present observation the larger EB field is found to be associated with the larger coercivity obtained from the MR-H curve which is in accordance with the proposed theories [29][30][31] as well as the experimental results [32][33][34]. Until now, different aspects of EB effect has been extensively investigated through the magnetization studies which is rather less focused in the MR measurement.…”
mentioning
confidence: 93%